Future Challenges of Photocatalytic Water Splitting: Sustainability - R.M. Aadarsh Vel; R. Madhumitha Sri; S. Ravichandran (International Journal of Photochemistry and Photochemical Research, 2025)
Photocatalytic water splitting has emerged as a promising technology for sustainable hydrogen production through the direct utilization of solar energy. This process mimics natural photosynthesis, using semiconductor materials to absorb light and drive the decomposition of water into hydrogen and oxygen. The method provides a sustainable and eco-friendly solution to the global energy challenge by enabling the reduction of carbon emissions. Among various solar-to-chemical energy conversion approaches, photocatalytic water splitting to generate hydrogen stands out as a particularly promising option. This light-driven process is regarded as an ideal renewable technology, capable of yielding high energy output without reliance on fossil fuels. In photocatalytic water splitting, water undergoes a redox reaction facilitated by photo-generated electrons and holes, resulting in the production of hydrogen. This review outlines the fundamental mechanisms of photocatalysts used for hydrogen evolution from aqueous media and discusses recent strategies for developing photocatalysts responsive to visible light. Recent advances have focused on engineering band structures, heterojunction formation, and surface modification to enhance charge separation efficiency and visible-light absorption. The incorporation of co-catalysts, defect engineering, and nanostructuring techniques has significantly improved photocatalytic activity and stability. Moreover, computational modeling and in-situ characterization methods have provided deeper insights into charge carrier dynamics and reaction pathways. Despite these advancements, challenges such as low quantum efficiency, photocorrosion, and scalability remain critical barriers to commercialization. Continued research integrating materials innovation, reaction kinetics, and reactor design optimization is essential to achieve efficient, cost-effective, and sustainable hydrogen production through photocatalytic water splitting.
Keywords: Hydrogen evolution; Photocatalytic water splitting; Semiconductor photocatalysts; Visible-light activation; solar energy conversion